2000
DOI: 10.1038/sj.cdd.4400710
|View full text |Cite
|
Sign up to set email alerts
|

CD40 ligand, Bcl-2, and Bcl-xL spare group I Burkitt lymphoma cells from CD77-directed killing via Verotoxin-1 B chain but fail to protect against the holotoxin

Abstract: Owing to its lineage and differentiation stage-restricted expression, CD77 has been mooted as a therapeutic target in Burkitt lymphoma (BL). The recognition that the globotriaosyl moiety of this neutral glycosphingolipid is a receptor for Escherichia coli-derived Verotoxin-1 (Shiga-Like Toxin-1) offers a potential delivery system for the attack. Here we show that CD77-expressing Group I BL cells which are normally susceptible to activation-induced death on binding Verotoxin-1 B chain are protected in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 57 publications
2
35
0
Order By: Relevance
“…Globotriaosyl ceramide (Gal␣(1-4)-Gal␤(1-4)-Glc␤1-ceramide) is differentially organized in glycolipid-enriched microdomains in mammalian membranes (44). After internalization of the holotoxin by receptor-mediated endocytosis, verotoxin inhibits protein synthesis resulting in necrosis and/or apoptosis (45)(46)(47). Whether RsAFP2-induced fungal growth arrest is a result of the induced membrane permeabilization or results from its interaction with a putative intracellular target is currently not known.…”
Section: Discussionmentioning
confidence: 99%
“…Globotriaosyl ceramide (Gal␣(1-4)-Gal␤(1-4)-Glc␤1-ceramide) is differentially organized in glycolipid-enriched microdomains in mammalian membranes (44). After internalization of the holotoxin by receptor-mediated endocytosis, verotoxin inhibits protein synthesis resulting in necrosis and/or apoptosis (45)(46)(47). Whether RsAFP2-induced fungal growth arrest is a result of the induced membrane permeabilization or results from its interaction with a putative intracellular target is currently not known.…”
Section: Discussionmentioning
confidence: 99%
“…In our present study, we used only the nontoxic STxB. It has been shown by several studies that STxB is capable of apoptosis induction in Burkitt's lymphoma cells, although it is not able to inhibit protein synthesis (33,36,38).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, different intracellular routing may play a pivotal role in cell susceptibility and triggering a different pathway for apoptosis. Stxinduced apoptosis and cytotoxicity are distinct processes (Gordon et al 2000;Williams et al 1999), although the A subunit can be necessary for apoptosis (Khine et al 2004). In our study, the same result was also shown, as if A subunit can separately induce apoptosis morphologically in higher concentration by Hoechst staining and DNA laddering method.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it has been shown that apoptosis is involved in the Stx-mediated cytotoxicity of the renal tubular and lung epithelium cell lines (Uchida et al 1999). In this case, apoptosis was maintained at Stx concentrations, wherein protein synthesis inhibition was prevented; therefore, Stx-induced apoptosis and cytotoxicity are two distinct processes (Gordon et al 2000;Williams et al 1999).…”
Section: Introductionmentioning
confidence: 99%